2007
DOI: 10.1111/j.1540-8175.2007.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Subclinical Cardiac Involvement in Systemic Sclerosis by Echocardiographic Strain Imaging

Abstract: Evaluation of ventricular function by using echocardiographic strain imaging appears to be useful to detect subclinical cardiac involvement in SSc patients with normal standard echocardiographic and tissue Doppler velocity findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
3
37
0
1
Order By: Relevance
“…However, there was a significant positive correlation between plasma BNP levels and E/A ratio, which has been suggested to provide a better reflection of LV diastolic function (14,21). Tissue Doppler parameters seem to be more sensitive in determining the subtle cardiac functional alterations than the conventional echocardiographic parameters (13,22). The negative correlations between RV peak systolic pulsed-wave tissue Doppler velocities and BNP levels in our study may indicate that BNP levels may also increase in case of RV systolic dysfunction, just as in LV dysfunction (23,24).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, there was a significant positive correlation between plasma BNP levels and E/A ratio, which has been suggested to provide a better reflection of LV diastolic function (14,21). Tissue Doppler parameters seem to be more sensitive in determining the subtle cardiac functional alterations than the conventional echocardiographic parameters (13,22). The negative correlations between RV peak systolic pulsed-wave tissue Doppler velocities and BNP levels in our study may indicate that BNP levels may also increase in case of RV systolic dysfunction, just as in LV dysfunction (23,24).…”
Section: Discussionmentioning
confidence: 92%
“…Since conventional transmitral Doppler parameters reflecting LV diastolic function [transmitral peak early diastolic filling velocity (E), transmitral peak late diastolic filling velocity (A), isovolumic relaxation time (IVRT) and E wave deceleration time (Edec)] are rather dependent on loading conditions, new echocardiographic techniques that are affected to a lower extent from preload and afterload were emerged in the recent years for evaluation of LV diastolic function [pulsed-wave Doppler tissue velocities, mitralcolor propagation velocity (mCP)]. Subclinical myocardial damage may be detected by the tissue Doppler method, even when the conventional echocardiographic parameters are normal (13). Pulsed-wave tissue Doppler velocities (both systolic and diastolic), strain (the total percentage of deformation of myocardial segment, the percentage of shape distortion) and strain rate (the rate of deformation in the unit time) parameters can be measured by using tissue Doppler analysis and these parameters can be used to document subtle myocardial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Strain and strain rate measurements appeared to be sensitive indicators for sub-clinical diseases, including arterial hypertension, diabetes, systemic sclerosis, myocardial ischemia, isolated mitral regurgitation and non-ischemic cardiomyopathies, and also very useful for the assessment of myocardial damage after myocardial infarction, evaluation of myocardial revascularization efficiency and prediction of patient outcome with heart failure [11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]. In a study on 137 consecutive patients with suspected congestive heart failure of different etiologies it was also shown that mean longitudinal LV strain is closely related to plasma brain-type natriuretic peptide (BNP) levels, in patients with both systolic and diastolic heart failure [42].…”
Section: Clinical Applications and Future Directions Of Echocardiogramentioning
confidence: 99%
“…It appears more sensitive than ejection fraction for detecting subtle abnormalities in LV myocardial function, but it is limited to longitudinal and radial deformation measurements [5] . TDI has been considered a reliable tool to point out subclinical cardiac involvement in systemic sclerosis patients who show normal standard echo parameters [6] ; moreover, Birdane et al [7] have demonstrated that RA patients have significant impairment of left and right ventricular TDI parameters compared to healthy controls. However, this method is limited by angle-dependency: whereas myocardium deforms simultaneously in three dimensions, and only deformation along the ultrasound beam can be derived from velocities with TDI [8] .…”
Section: Introductionmentioning
confidence: 99%